Driving Customer Loyalty in Digital Banking: The Strategic Role of Digital Marketing, Service Quality, and Customer Experience - Ega Susanto, Setya; Maricar, Rezvanny; Baharuddin, Ceskakusumadewi; Panus, Panus; Sasmita, Halida (Jurnal Manajemen Perbankan Keuangan Nitro, 2026)
The rapid development of digital technology has significantly transformed the banking industry, compelling banks to adopt integrated digital marketing strategies to remain competitive and enhance customer relationships. This study aims to examine the influence of digital marketing strategy on customer loyalty in the banking industry by incorporating digital service quality, customer experience, and customer satisfaction into a comprehensive structural model. A quantitative research design was employed using a cross-sectional survey of 250 digital banking users who had actively utilized mobile or internet banking services for at least six months. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that digital marketing strategy has a significant positive effect on digital service quality and customer experience. Digital service quality significantly influences customer satisfaction and customer loyalty, while customer satisfaction and customer experience both positively affect customer loyalty. Furthermore, mediation analysis reveals that customer satisfaction partially mediates the relationship between digital service quality and customer loyalty, and customer experience partially mediates the relationship between digital marketing strategy and customer loyalty. The model demonstrates substantial explanatory power, with digital marketing-related constructs explaining a significant proportion of variance in customer loyalty. The findings suggest that digital marketing strategy functions not merely as a promotional tool but as an integrated system that enhances service performance, personalization, and customer engagement. By effectively managing digital touchpoints, CRM systems, and service quality dimensions, banks can strengthen customer satisfaction and foster long-term loyalty. This study contributes to the literature by extending traditional service quality and satisfaction–loyalty frameworks into the digital banking context and offers practical implications for banks seeking sustainable competitive advantage in the era of digital transformation.